La dinámica económica de Harrod y el paradigma Keynesiano - Sancho, Alejandro (1999)
The standard interpretation of Harrod' s economics dynamics heavily dependent on the so-called “Harrod-Domar“ model of economics growth is misleading for an accurate assessment of Harrod' s model. In arder to do that this articles explores the connection between Harrod 's economics dynamics and Keynes' work by showing how sorne key analytical tools and the “vision“, in a schumpeterian sense, for the formulation of an economics dynamics in Harrod are based on, or developed from, Keynes's General Theory and his criticism to the “classical economics“. Keynes' influence is observed in the general structure of the model and on the mechanisms under which is analyzed the long-term economic growth. It is intended to show those key elements that make evident that and the degree of their importance in the mathematical structure of the model and in the extent of Harrod's conclusions. With that aims is examined comparatively sorne chief points as the rol of the savinginvestment process, the rol of supply factors, the implicit notion of time, the significance of fu// employment equilibrium and the notion of equilibrium employed in the analysis of growth.